COVID-19 Mortality Trends over the First Five Years of the Pandemic in the US - Camilla Mattiuzzi; Giuseppe Lippi (COVID, 2025)
Background/Objectives: This retrospective observational study investigated coronavirus disease 2019 (COVID-19)-related mortality trends in the US throughout the pandemic. Methods: We performed a retrospective, descriptive analysis between 2020 and 2024 using data from the US National Center for Health Statistics. Results: The total number of COVID-19 deaths rose by 19% from 2020 to 2021, followed by a significant decline in the subsequent years, with an average reduction factor of 0.44. Mortality rates remained higher in males compared to females, with a gender disparity between 52 and 62%. Age-specific crude mortality rates increased with advancing age, with higher mortality observed in older populations. However, crude death rates significantly declined across all ages except for the 1–4 years group, which experienced a 33% increase. The majority of fatalities occurred in medical facilities (63–80%), but this proportion gradually decreased over time, while the percentage of deaths occurring at home nearly doubled from 2020 to 2024 (6% to 11%). Conclusions: The initial mortality peak for COVID-19 was followed by a substantial decline, likely influenced by the widespread availability of vaccines, improvements in clinical management, and the emergence of less virulent variants. The persistent gender and age disparities, alongside the fluctuating distribution of the places of death, offer insights for refining healthcare policies and optimizing resource allocation in this and other future pandemics.